The Tenasserim Banyan - Turner, I. M. (Phytotaxa, 2012)
In his Natural Productions of Burma published in 1850, Francis Mason described a fig species that he referred to as the Tenasserim Banyan and legitimately published the name Ficus benjaminoides for it. This name has been very largely overlooked in the botanical literature. In the absence of type material, the name is here neotypifed to make F. benjaminoides Mason a synonym of Ficus benjamina. Mason’s name makes Ficus benjaminoides Corner an illegitimate later homonym.